Łódź Region and its Northern Vicinity under Vistulian Glaciation Conditions - Roman, Małgorzata; Dzieduszyńska, Danuta; Petera-Zganiacz, Joanna (Quaestiones Geographicae, 2014)
An overview of palaeogeographical findings of the last glacial period (MIS 5d-MIS 2) has been given for the Łódź region. Processes which influenced the area outside of ice-sheet margin are presented with respect to space and time, as predominantly driven by different types of periglacial environment. Attention was paid to leading accumulative and erosional processes and resulting landforms, still well-pronounced in the landscape. Recently, the picture of the area discussed, during the Vistulian was completed and identified was the mechanism of the LGM ice-sheet advance onto the Płock lobe. Borderline location of the Łódź region offers comprehensive research on the time and processes and determines its significance on the geomorphological map of Poland.